2023
DOI: 10.1039/d2re00357k
|View full text |Cite
|
Sign up to set email alerts
|

An electron “donor–acceptor–donor” strategy to activate ZIF-67 as a cathode material for fuel cells and zinc ion hybrid supercapacitor

Abstract: Rational design of non-precious and efficient electrocatalyst for oxygen reduction reaction (ORR) is of utmost importance for sustainable energy exploitation, to solve the energy crisis and environmental jeopardy. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Benefitted by the synergy between high specific surface area, high pore volume, and abundant heteroatom contents, the S, N-CNC-based ZIHSCs have demonstrated excellent energy–power combination, as shown in the Ragone plot (Figure e). Notably, the energy density of the as-assembled Zn//S, N-CNC ZIHSC could reach 148.9 W h kg –1 at a power density of 900 W kg –1 (based on the mass loading of active material on the cathode), which is significantly better than most of the ZIHSCs reported in recent times, including NPG//ZnSO 4 //Zn, AC//ZnSO 4 //Zn, WC6ZnN-12 U//ZnSO 4 //Zn, MSCP//ZnSO 4 //Zn, NPC//ZnSO 4 //Zn, Al-Co/NGC-800//ZnSO 4 //Zn, and NSPCN-800//ZnSO 4 //Zn . Moreover, even at a high current rate, the ZIHSC could deliver an energy density of 60.6 W h kg –1 at a high power density of 7.2 kW kg –1 .…”
Section: Resultsmentioning
confidence: 82%
“…Benefitted by the synergy between high specific surface area, high pore volume, and abundant heteroatom contents, the S, N-CNC-based ZIHSCs have demonstrated excellent energy–power combination, as shown in the Ragone plot (Figure e). Notably, the energy density of the as-assembled Zn//S, N-CNC ZIHSC could reach 148.9 W h kg –1 at a power density of 900 W kg –1 (based on the mass loading of active material on the cathode), which is significantly better than most of the ZIHSCs reported in recent times, including NPG//ZnSO 4 //Zn, AC//ZnSO 4 //Zn, WC6ZnN-12 U//ZnSO 4 //Zn, MSCP//ZnSO 4 //Zn, NPC//ZnSO 4 //Zn, Al-Co/NGC-800//ZnSO 4 //Zn, and NSPCN-800//ZnSO 4 //Zn . Moreover, even at a high current rate, the ZIHSC could deliver an energy density of 60.6 W h kg –1 at a high power density of 7.2 kW kg –1 .…”
Section: Resultsmentioning
confidence: 82%
“…It has a typical zeolite topological structure with abundant pores . Due to excellent chemical and thermal stability, ZIF-67 and its derivatives have potential applications in fields such as adsorption and separation, , electrode material, , biomedicine, , and catalysis. , In general, the physical and chemical properties of ZIF-67 are determined by particle morphology and size. ,, Chen et al investigated the antibacterial activity of ZIF-67 against Saccharomyces cerevisiae and found that the ZIF-67 nanocube performed better than the ZIF-67 rhombic dodecahedron, and the smaller the size of ZIF-67, the poorer the antibacterial activity. Li et al demonstrated that ZIF-67 showed adjustable CO 2 adsorption behaviors during the evolution from the 3D to 2D phase.…”
Section: Introductionmentioning
confidence: 99%
“…19 High temperature-treated ZIF-based electrocatalysts show improved conductivity and produce atomically dispersed M-Nx type active centres. 20 The active centres that are located at the electrode-electrolyte interface contribute to the electrocatalytic activity, while those trapped inside the deep carbon network are electrochemically inactive. 16 Although there are several reports on ZIF based electrocatalysts confirming their high electrochemical activity in terms of the number of active catalytic centres, surface area, porosity and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, pyrolysis is one of the preferred techniques 19 . High temperature‐treated ZIF‐based electrocatalysts show improved conductivity and produce atomically dispersed M‐Nx type active centres 20 . The active centres that are located at the electrode‐electrolyte interface contribute to the electrocatalytic activity, while those trapped inside the deep carbon network are electrochemically inactive 16 .…”
Section: Introductionmentioning
confidence: 99%